Garbage: contamination and solution through composting techniques and beneficial results for sustainable agriculture - Oliveira, Luísa Helena dos Santos; Oliveira, Maria Carolina Marques de; Oliveira, Marcelo Tavares de (Revista Hipótese, 2020)
The importance of the use of urban solid waste for recycling and manufacturing of organic compost is related to its economic and social feasibility. In this context, composting may be favored as an alternative to waste treatment when compared to the costs of conventional waste disposal methods. Different combinations of sugarcane bagasse, litter and chicken and fair residue were used in order to establish the best conditions for the production of organic fertilizer, beneficial for sustainable agriculture. After the qualitative evaluation of the organic fertilizer, it was concluded that the sugarcane bagasse, followed by the clean show, present a balanced